Estado e industrialización en el Ecuador, 1948-2021 - Creamer Guillén, Claudio Alonso (2022)
Historic record of Ecuadorian industry from 1920 to 1948, followed by the developmentalism incorporated between 1958 and 1960, and the developmental state from 1960 to 1972, oriented to an ECLAC industrial policy, which was deepened during the first oil boom (1972-1981). Between 1982 and 2006, with the foreign debt crisis, the import substitution industrial policy were dismantled and an export model was promoted.  During the Correa administration (2007-2017) a neodevelopmentalist industrial policy was formulated, aimed at changing the productive matrix during the second oil boom (2004-2014). The Moreno government (former vice president of Correa), from 2017 to 2021, modified the economic model towards a market-oriented economy.